One-Year Outcomes After Minimally Invasive Sacrocolpopexy. Issue 5 (September 2016) - Kenton, Kimberly; Mueller, Elizabeth R.; Tarney, Christopher; Bresee, Catherine; Anger, Jennifer T.
Abstract : Objective: The primary aim of this study was to report anatomic, symptom, and quality of life outcomes in women with symptomatic stage 2 or greater prolapse 1 year after randomization to robotic and laparoscopic sacrocolpopexy. Methods: This is a planned ancillary analysis of the Abdominal Colpopexy: Comparison of Endoscopic Surgical Strategies trial, a randomized comparative effectiveness trial comparing costs and outcomes of robotic and laparoscopic sacrocolpopexy at 2 academic medical centers. At baseline and 1 year after surgery, women underwent standardized assessment including validated subjective pelvic floor outcomes and physical examination with prolapse assessment. Results: Sixty six (85%) of 78 randomized participants completed 1-year follow-up: 33 (87%) of 38 in the laparoscopic arm and 33 (83%) of 40 in the robotic arm ( P = 0.59). Ninety-seven percent (32/33) in the laparoscopic group and 100% (33/33) in the robotic arm considered that their prolapse symptoms improved ( P = 0.999). The cohort had significant improvement in all pelvic floor symptom and quality of life measures, which did not differ by treatment arm. Of women who were sexually active at 1 year, sexual function improved in both cohorts. No new serious adverse events, including mesh exposure or reoperation for prolapse, were identified between 6 months and 1 year after surgery. No women had a sacrocolpopexy mesh complication or reoperation for mesh exposure. Conclusions: Minimally invasive sacrocolpopexy is associated with significant improvement in pelvic floor symptoms, anatomy, and sexual function. In addition, mesh exposure rates with lightweight polypropylene mesh seem to be lower than those reported with multifilament and heavier polypropylene mesh. Abstract : Minimally invasive sacrocolpopexy is associated with significant improvement in pelvic floor symptoms, anatomy, and sexual function.